Analysis of Road Network Pattern Considering Population Distribution and Central Business District. - Fangxia Zhao; Huijun Sun; Jianjun Wu; Ziyou Gao; Ronghui Liu (PLoS ONE, 2016)
This paper proposes a road network growing model with the consideration of population distribution and central business district (CBD) attraction. In the model, the relative neighborhood graph (RNG) is introduced as the connection mechanism to capture the characteristics of road network topology. The simulation experiment is set up to illustrate the effects of population distribution and CBD attraction on the characteristics of road network. Moreover, several topological attributes of road network is evaluated by using coverage, circuitness, treeness and total length in the experiment. Finally, the suggested model is verified in the simulation of China and Beijing Highway networks.